Edukasi Normatif-Ekonomi Perkreditan dan Jaminan Perbankan sebagai Upaya Peningkatan Pendapatan Pekerja di Sumatera Utara - Nikmah Dalimunthe; Cici El Dirrah Syafitri; Abdurrahman Abdurrahman; Lathifa Ananda Putri; Miratul Imaniah; Muhammad Iqbal; Mulia Syaputri; Niswa Auliya Lubis; Ruli Pebrina Br Sitepu; Septian Dwi Cahya; Vany Fadilah Bastian; Aulia Syafitri; Najwa Nabila (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to increase the understanding and capacity of workers, especially Micro, Small, and Medium Enterprises (MSMEs) related to credit and banking guarantee practices from a normative and economic perspective, as well as their relevance to increasing workers' income in North Sumatra. The problems faced by partners include low legal and economic literacy in banking, limited understanding of credit guarantee mechanisms, and lack of optimal use of productive financing. The service methods used include educational and socialization activities through material presentations, interactive discussions, and evaluation of participants' understanding using pre-test and post-test. The material provided includes banking credit regulations, types of credit guarantees such as dependents and fiduciary guarantees, as well as strategies for the use of productive credit to increase income. The results of the activity showed an increase in participants' understanding of the normative aspects of credit and banking guarantees, as well as increased awareness in choosing and managing credit in a more productive and sustainable manner. This activity makes a practical contribution in the form of strengthening financial literacy and banking laws which is expected to encourage an increase in workers' income in an inclusive manner in North Sumatra.